Discovery of cryptotephra at Middle–Upper Paleolithic sites Arma Veirana and Riparo Bombrini, Italy: a new link for broader geographic correlations - Jayde N. Hirniak; Eugene I. Smith; Racheal Johnsen; Minghua Ren; Jamie Hodgkins; Caley Orr; Fabio Negrino; Julien Riel‐Salvatore; Shelby Fitch; Christopher E. Miller; Andrea Zerboni; Guido S. Mariani; et al. (Journal of Quaternary Science, 2020)
Chemical characterization of cryptotephra is critical for temporally linking archaeological sites. Here, we describe cryptotephra investigations of two Middle–Upper Paleolithic sites from north‐west Italy, Arma Veirana and Riparo Bombrini. Cryptotephra are present as small ( 75 wt.%) with low FeO ( 2 O/Na 2 O > 1 and P2 is also a high silica rhyolite (>75 wt.%) but with higher FeO (2.33–2.65 wt.%). Shards at Riparo Bombrini (P3) are of the same composition as P1 shards at Arma Veirana, providing a distinct link between deposits at both sites. Geochemical characteristics suggest three possible sources for P1 and P3: eruptions from Lipari Island (56–37.7 ka) in Italy, the Acigöl volcanic field (200–20 ka) in Turkey and the Miocene Kirka‐Phrigian caldera (18 Ma) in Turkey. Eruptions from Lipari Island are the most likely source for P1,3 cryptotephra. This study highlights how cryptotephra can benefit archaeology, by providing a direct link between Arma Veirana and Riparo Bombrini as well as other deposits throughout the Mediterranean.